Political Behaviour of the Indonesian Middle Class: Lower Turnouts in More Modernised Areas - Margani Utami, Dyah; Ikhsan, Mohamad; Dartanto, Teguh; Mallarangeng, Rizal (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
The modernisation theory assumes that the larger the middle class, the more likely democracy is supported; for example, there will be more participation in elections, as shown in Western countries. However, there is no clear evidence on whether this trend also appears in developing countries. This study emphasises the association between the proportion of the middle class and the support for democracy in terms of voter turnout. Irrespective of the nature of the elections, we suppose that the modernisation level, proxied by the middle-class share, determines voter turnouts. Using data from Statistics Indonesia (BPS) and the General Election Commission (KPU), we differentiate the voter turnouts in Indonesia's general election in 2019 at the district or city levels by grouping them into modernised and less-modernized regions, i.e., urban versus rural, Java versus outside Java, and western versus eastern regions. This study documented a deviation from the modernisation theory, evidenced by an unclear association between the proportion of the middle class and the voter turnout in the modernised areas. Counterintuitively, there are positive associations in the less modernised areas. The findings also reveal the selective participation among voters, as they showed different participation levels in the types of elections conducted in one day. They were more active in presidential elections than in parliamentary elections. In developing countries like Indonesia, the expansion of the middle class, followed by the declining number of rural regions, may lead to a decline in voter turnouts, thus raising demand for good governance and better performance of parties and candidates.